A New Surgical Procedure "Dumbbell-Form Resection" for Selected Hilar Cholangiocarcinomas With Severe Jaundice: Comparison With Hemihepatectomy. Issue 2 (January 2016) - Wang, Shuguang; Tian, Feng; Zhao, Xin; Li, Dajiang; He, Yu; Li, Zhihua; Chen, Jian
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of the study is to evaluate the therapeutic effect of a new surgical procedure, dumbbell-form resection (DFR), for hilar cholangiocarcinoma (HCCA) with severe jaundice. In DFR, liver segments I, IVb, and partial V above the right hepatic pedicle are resected. Hemihepatectomy is recognized as the preferred procedure; however, its application is limited in HCCAs with severe jaundice. Thirty-eight HCCA patients with severe jaundice receiving DFR and 70 receiving hemihepatectomy from January 2008 to January 2013 were included. Perioperative parameters, operation-related morbidity and mortality, and post-operative survival were analyzed. A total of 21.1% patients (8/38) in the DFR group received percutaneous transhepatic biliary drainage (PTBD), which was significantly <81.4% (57/70) in the hemihepatectomy group. The TBIL was higher in the DFR group at operation (243.7 vs 125.6 μmol/L, respectively). The remnant liver volume was significantly higher after DFR. The operation-related morbidity was significantly lower after DFR than after hemihepatectomy (26.3% vs 48.6%, respectively). None of the patients died during the perioperative period after DFR, whereas 3 died after hemihepatectomy. There was no difference in margin status, histological grade, lymph-node involvement, and distant metastasis between the 2 groups. The 1-, 3-, and 5-year survival rates after DFR (68.4%, 32.1%, and 21.4%, respectively) showed no significant difference with those after hemihepatectomy (62.7%, 34.6%, and 23.3%, respectively). Kaplan–Meier analysis indicated that overall survival and recurrence after DFR demonstrated no significant difference compared with hemihepatectomy. DFR appears to be feasible for selected HCCA patients with severe jaundice. However, its indications should be restricted.